Systemic Immune-Inflammatory Index, Tumor-Infiltrating Lymphocytes, and Clinical Outcomes in Esophageal Squamous Cell Carcinoma Receiving Concurrent Chemoradiotherapy - Jun Yang; Jifang Zheng; Jianjian Qiu; Mengyan Zhang; Lingyun Liu; Zhiping Wang; Qunhao Zheng; Yanyan Liu; Mingqiu Chen; Jiancheng Li (Journal of Immunology Research)
Background. Systemic inflammation may be involved in the entire cancer process as a promoter and is associated with antitumor immunity. The systemic immune-inflammation index (SII) has been shown to be a promising prognostic factor. However, the relationship between SII and tumor-infiltrating lymphocytes (TIL) have not been established in esophageal cancer (EC) patients receiving concurrent chemoradiotherapy (CCRT). Methods. Retrospective analysis of 160 patients with EC was performed, peripheral blood cell counts were collected, and TIL concentration was assessed in H&E-stained sections. Correlations of SII and clinical outcomes with TIL were analyzed. Cox proportional hazard model and Kaplan–Meier method were used to perform survival outcomes. Results. Compared with high SII, low SII had longer overall survival (OS) (P=0.036, hazard ratio (HR) = 0.59) and progression-free survival (PFS) (P=0.041, HR = 0.60). Low TIL showed worse OS (P<0.001, HR = 2.42) and PFS (P<0.001, HR = 3.05). In addition, research have shown that the distribution of SII, platelet-to-lymphocyte ratio, and neutrophil-to-lymphocyte ratio were negatively associated with the TIL state, while lymphocyte-to-monocyte ratio presented a positive correlation. Combination analysis observed that SIIlow + TILhigh had the best prognosis of all combinations, with a median OS and PFS of 36 and 22 months, respectively. The worst prognosis was identified as SIIhigh + TILlow, with a median OS and PFS of only 8 and 4 months. Conclusion. SII and TIL as independent predictors of clinical outcomes in EC receiving CCRT. Furthermore, the predictive power of the two combinations is much higher than a single variable.